Infusion device standardisation and dose error reduction software. - Iacovides, Ioanna; Blandford, Ann; Cox, Anna; Franklin, Bryony Dean; Lee, Paul; Vincent, Chris J. (British Journal of Healthcare Management, 2015)
In 2004, the National Patient Safety Agency (NPSA) released a safety alert relating to the management and use of infusion devices in England and Wales. The alert called for the standardisation of infusion devices and a consideration of using centralised equipment systems to manage device storage. There has also been growing interest in smart-pump technology, such as dose error reduction software (DERS) as a way to reduce IV medication errors. However, questions remain about the progress that has been made towards infusion device standardisation and the adoption of DERS. In this article, the authors report the results of a survey investigating the extent to which the standardisation of infusion devices has occurred in the last 10 years and centralised equipment libraries are being used in practice, as well as the prevalence of DERS use within the UK. Findings indicate that while reported standardisation levels are high, use of centralised equipment libraries remains low, as does DERS usage.